МАКРОМАРКЕТИНГ КАК ИНСТРУМЕНТ ГОСУДАРСТВЕННОГО РЕГУЛИРОВАНИЯ В ПРОМЫШЛЕННОЙ СФЕРЕ. (Journal of Economic Research & Business Administration, 2015)
Макромаркетингтiң кешенi – ұлттық экономика дамуының тиiмдi аспаптарының бiрi. Қазақстандық үкiметкейбiр макромаркетингтiң бiр бөлiктерiн қолданады, бiрақ біздің елде бiртұтас макромаркетинг жиынтығыныңтиiмдi қолдануы туралы айту әлi ерте.***Complex of macromarketing is one of the most efficient instruments of developing national economics. Kazakhgovernment uses some parts of macromarketing, but it is too early to speak about efficient use of wholemacromarketing complex in our country.